Effect of Malathion on Physio-Biological Aspects of Notopterus notopterus (Pallas) - Ahirwar, Manoj kumar; Shammi, Q . J .; Chalko, Salman Raouf; Lone, Gh. Nabi (Asian Journal of Biological and Life Sciences, 2012)
During the present experiment, N. notopterus were exposed to lethal concentration (0.1 ppm) of malathion for a period of 03 hours in triplicates. A marked reduction in the opercular beat frequency (92.3 to 45.3) and tail beat frequency (7.3 to 4.3) was observed after the exposure. The results on the haematological aspect of the experiment (5 replicas) revealed that significant (P<0.05) increase in WBC (6.06 to4.58), and reduction in Hb, RBC, PCV, MCV, MCH, MCHC and other non-specific defense cells. The increase in the WBC count is due to the non-specific immune response of the fish.